Revisiting the Gramscian Legacy on Counter-Hegemony, the Subaltern and Affectivity: Toward an Emotional Pedagogy of Activism in Higher Education - Zembylas, Michalinos (Critical Studies in Teaching and Learning, 2023)
This paper seeks to revisit Gramsci’s legacy on counter-hegemony, the subaltern and affectivity, by focusing on the implications of his cutting-edge position on the role of subaltern feelings in the formation of an emotional pedagogy of activism in the context of higher education. Three insights follow from this analysis. First, Gramsci’s work facilitates an understanding of how affect and ideology are entangled. Second, Gramsci’s concepts of counter-hegemony, the subaltern, and the organic intellectual in relation to his views about the unity of reason and emotion offer points of departure for activism, especially small acts of everyday life that often go unnoticed. Finally, Gramsci’s concern with the emotional potential of subaltern subjects shows how important it is to consider subaltern passions as political resources that challenge hegemonic conditions and formulate strategic counter-hegemonic responses.